3, 4-Diaminopyridine (amifampridine) for the treatment of Lambert–Eaton myasthenic syndrome. (March 2014) - Lindquist, Sabine; Stangel, Martin
<x xml:space="preserve">Abstract</x> Introduction: Lambert–Eaton myasthenic syndrome (LEMS) is an autoimmune disorder of the neuromuscular junction resulting in muscle weakness and autonomic symptoms. LEMS often occurs as a paraneoplastic disease. Hallmarks of the disease are pathogenic antibodies against voltage-gated calcium channels, which cause a decrease in presynaptic acetylcholine release. <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=3, 4-Diaminopyridine&logicalOpe1=OR&field2=articletitle&text2=3, 4-Diaminopyridine&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">3, 4-Diaminopyridine (3, 4-DAP) is a potassium channel blocker, which leads to an increase of presynaptic calcium and improves the release of acetylcholine in LEMS patients. Areas covered: Here, the role of 3, 4-DAP for the treatment of LEMS is reviewed. A literature search was carried out for the terms '3, 4-diaminopyridine' and 'Lambert–Eaton myasthenic syndrome'. The information updates a previous review on the topic. Expert opinion: Small placebo-controlled studies have shown the efficacy of 3, 4-DAP to treat muscle weakness in LEMS patients. A larger drug withdrawal study analyzing 30 patients on stable treatment with 3, 4-DAP is under way. The efficacy of 3, 4-DAP is moderate. There is a need to study the additional effects of pyridostigmine, a drug inhibiting acetylcholine breakdown used in myasthenia gravis, and the potential of novel calcium channel agonists. Apart from treating LEMS symptoms, 3, 4-DAP may also be beneficial in the treatment of congenital myasthenic syndromes and myasthenia gravis caused by anti-muscle-specific kinase-antibodies.